A imigração haitiana para o Brasil: um olhar a partir do sintagma identidade-metamorfose-emancipação - Miranda, Suélen Cristina de (2017)
In view of the relevance assumed by the contemporary migratory phenomenon in the so-called era of migrations and the multiplicity of approaches that it encompasses, this work was based on the perspective of "Critical Social Psychology" to propose an approach that would denaturalize the term migrant and take into account the unique perception of the migrant in relation to the determinations to which it is subjected. It was then considered the framework of expulsion that was consolidated in Haiti and established migration as an important identity option, as well as Brazilian identity policies that directly influence the insertion of each migratory group. The objective was to understand the process of identity formation of Haitians living in Brazil in the light of the syntagma identity-metamorphosis-emancipation, proposed by Ciampa (2005), analyzing possible emancipatory fragments in the migratory process. The relevance of this study is manifested in the contemporaneousness and magnitude of the Haitian flow to Brazil and a lack of studies with the perspective of identity it, which can contribute to the development of effective public policies and to overcome stereotypes that impede a citizen's insertion of immigrants. The method was based on the comprehensive model, using the life history narrative as an instrument for the data collection of three Haitian immigrants, established in São Paulo and considered emblematic subjects. The maxim that "the singular materializes the universal" allowed the understanding of the "Haitian immigrant" character, noting that immigration, even forced, allows the rupture with the reckless replacement of daily life and the experience of new identity possibilities, built with more autonomy and which make possible the development of emancipatory fragments. It is in this sense that the process of identity reconstruction caused by the migratory process ends up generating "hybrid identities", recreated from tradition, however translated into new relationships, resulting in processes of self-understanding and a constant search to transform external determinations into self-determination. The relevance of an identity claim built as self-affirmation and hetero-recognition of an emancipatory project also reveals the effects of perverse recognition on the contradiction — always present in the migrant condition — between temporary and permanent